A General Microsimulation Model for the EU VAT with a specific Application to Germany - Lars-H. R. Siemers (Philipps-University Marburg, Faculty of Business Administration and Economics, 2014)
The sales taxes in the EU - and in several other countries - are practiced as value-added tax of the consumption type with invoice method. Literature on microsimulation models (MSM) for this type of VAT is rare, though the importance of VAT has continuously increased. We discuss the issues of VAT-MSM in detail and develop a basic general VAT-MSM, applicable to the EU member states (and beyond). To illustrate the functioning of the general model, we apply it in detail to the specific case of Germany. We provide comprehensive estimation results for the distributional and fiscal effects of the German VAT. Finally, we simulate the effects of a small VAT reform in 2010, comparing static and behavioral response simulations.
Keywords: H22; H24; C6; D12; D31; D63; 330; VAT microsimulation VAT exemption RWI-VAT-SIM EU